Measurement of the pep and CNO solar neutrino interaction rates in borexino - Davini, Stefano (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2014)
Solar neutrino experiments have proved to be sensitive tools to test both astrophysical and elementary particle physics models. Neutrinos coming from the Sun offer a window into the inner workings of our star. Both the first evidence and the first discoveries of neutrino oscillations have come from experiments which detected neutrinos from the Sun. The Borexino experiment at Laboratory Nazionali del Gran Sasso is designed to perform solar neutrino spectroscopy below 2 MeV. The key feature that allow Borexino to pursue this physics program is its ultra low background level. This thesis is devoted to the first direct measurement of the pep and CNO solar neutrino interaction rates in the Borexino experiment. The detection of the rare signals from pep and CNO solar neutrinos in Borexino requires novel analysis techniques, as the signal interaction rate in the active target is only a few counts per day, while the dominant background in the relevant energy region, the cosmogenic beta+ emitter carbon-11, produced in Borexino by cosmic muon interactions, is about 10 times higher.